2022
DOI: 10.4103/jfmpc.jfmpc_2350_21
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of remdesivir and its effect on oxygen desaturation: A clinical review study among high-risk COVID-19 patients in Myanmar

Abstract: Background: Although Remdesivir has been evaluated for the treatment of coronavirus disease 2019 (COVID-19), few study has yet shown effective mortality reduction. It might be because, in almost all those studies, remdesivir therapy was started beyond 7 th days from the onset of symptoms when the active viral replications have already gone. Methods: This study reviewed the effectiveness of early remdesivir therapy during viral phase of COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Randomized controlled trials (RCT) have confirmed this null effect that recruited similar cohorts conducted in high and upper-middle-income countries [ 9 ]. A shorter SORT interval of fewer than three days did not confer a mortality benefit, contradicting previous studies [ 10 , 11 ]. However, our study design limits the validity of these interpretations.…”
Section: Discussioncontrasting
confidence: 89%
“…Randomized controlled trials (RCT) have confirmed this null effect that recruited similar cohorts conducted in high and upper-middle-income countries [ 9 ]. A shorter SORT interval of fewer than three days did not confer a mortality benefit, contradicting previous studies [ 10 , 11 ]. However, our study design limits the validity of these interpretations.…”
Section: Discussioncontrasting
confidence: 89%
“…Apart from pivotal studies, limited real-world data supporting the effectiveness of early remdesivir therapy in decreasing the overall risk of hospitalization and disease progression in SARS-CoV-2 high-risk outpatients are currently available ( 14 , 15 ). In addition, real-life data focusing on the safety and effectiveness of early remdesivir among the elderly are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Early administration of a 5-day course of remdesivir (within two days of admission) was associated with a significantly shorter time to clinical improvement, lower viral load [ 26 ] and positive IgG antibodies, reduced length of hospital stay, and lower risk of in-hospital death [ 27 ]. In another retrospective single-center study, the threshold of clinical benefit was set to 9 days from symptom onset for the initiation of RDV when significantly lower all-cause mortality was documented ( p = 0.004) [ 28 ]. Keeping in mind that testing is delayed for several days following manifestations, other authors showed that if RDV was initiated within three days of a positive test result, the length of stay was shorter ( p = 0.03), in addition to the mortality rate and the need for MV [ 29 ].…”
Section: Remdesivir Outcomesmentioning
confidence: 99%